Assessment of farmer’s knowledge and attitudes toward fungi and mycotoxin contamination in staple crops in southern Mozambique - Bila, João; Macuamule, Custódia; Bombe, Amina; Ribeiro, Maria Isabel; Venâncio, Armando; Afonso, Sandra; Rodrigues, Paula (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn Mozambique, 80% of the population directly depends on agriculture as a source of food and income. However, some of the most produced food crops, such as maize, rice and peanuts, are easily contaminated by fungi and mycotoxins. The naturally high prevalence of mycotoxins can be aggravated by the high vulnerability and lack of knowledge of the farmers. The aims of this study were to assess the knowledge and perceptions of small-size and medium-size farmers in the provinces of Inhambane and Gaza, southern Mozambique, regarding awareness of fungi and mycotoxin contamination of food crops, losses of production and income, and the causes and consequences of this contamination.MethodsA survey was conducted with 180 farmers in the two provinces. A multiple linear regression model was used to correlate the level of knowledge with the sociodemographic characteristics of the studied population.ResultsThe results showed that 97.8% of the farmers have an insufficient level of knowledge about fungi and mycotoxins contamination of food crops. While 17.8% showed sufficient or good knowledge of the conditions that promote fungal contamination, only 3.9% knew what measures to apply to mitigate their occurrence. The level of knowledge was lower for the Inhambane farmers.DiscussionAccording to the estimated model, province, gender, age (>45 years old), primary and secondary (1st cycle) education, another source of income other than agriculture and experience as a farmer (>10 years) are statistically significant predictors of the level of knowledge of the Mozambican farmers analyzed. These findings highlight the urgent need of tailored interventions to promote good agricultural and storage practices that allow the mitigation of mycotoxin contamination of food.